Comparison of injury incidences between football teams playing in different climatic regions - Orchard, J. W.; Walden, M.; Hägglund, M.; Orchard, J. J.; Chivers, I.; Seward, H.; Ekstrand, J. (Open Access Journal of Sports Medicine, 2013)
Australian Football League (AFL) teams in northern (warmer) areas generally have higher rates of injury than those in southern (cooler) areas. Conversely, in soccer (football) in Europe, teams in northern (cooler) areas have higher rates of injury than those in southern (warmer) areas, with an exception being knee anterior cruciate ligament (ACL) injuries, which are more common in the southern (warmer) parts of Europe. This study examined relative injury incidence in the AFL comparing 9,477 injuries over 229,827 player-weeks from 1999-2012. There was a slightly higher injury incidence for teams from warmer parts of Australia (relative risk [RR] 1.05, 95% confidence interval [CI] 1.01-1.10) with quadriceps strains (RR 1.32, 95% CI 1.10-1.58), knee cartilage injuries (RR 1.42, 95% CI 1.16-1.74), and ankle sprains (RR 1.17, 95% CI 1.00-1.37) all being more likely in warmer region teams. Achilles injuries followed a reverse pattern, tending to be more common in cooler region teams (RR 0.70, 95% CI 0.47-1.03). In conclusion, common findings from the AFL and European soccer are that ankle sprains and ACL injuries are generally more likely in teams playing in warmer climate zones, whereas Achilles tendinopathy may be more likely in teams playing in cooler zones. These injuries may have climate or surface risk factors (possibly related to types and structure of grass and shoe-surface traction) that are universal across different football codes.